Pastabos aukščiausiojo laipsnio formų istorijai - Zinkevičius, Zigmas (Baltistica, 2010)
REMARKS ON THE HISTORY OF SUPERLATIVE FORMS The name of the village Juodáusiai allows the reconstruction of the form *juodáusis ‘extremely black’ of the adjective júodas ‘black’. The superlative suffix -áusi(a)s could have originated from the semantically related words daũg < *dáug, dáuginti ‘many, much, multiply’ with the acute diphthong áu. The ending -sis is copied from pronominal adjectives, cf. juodàsis ‘black’. Due to the impact of didỹsis ‘great’, gen. sg. dìdžiojo, the form juodžiáusi(a)s emerged next to juodáusi(a)s. Thus, the imitation of the model of pronominal adjectives could have influenced the eventual formation of the superlative suffix -iáusias.